The Influence of Good Corporate Governance , Firm Size, Liquidity, and Dividend Payout Ratio on Firm Value in IDX80 Companies Listed on the Indonesia Stock Exchange for the Period 2020-2024 - Dewi Rismawati; Okta Karina Hardanti (JURNAL ECONOMINA, 2026)
This study aims to analyze the influence of Good Corporate Governance , firm size , liquidity , and dividend payout ratio on Firm Value in companies included in the IDX80 index on the Indonesia Stock Exchange during the period 2020–2024. The study uses a quantitative approach with an associative design and utilizes secondary data obtained from financial statements, annual reports, and company stock price data. The research sample consisted of 22 companies selected using a purposive sampling technique based on consistency of membership in the index, completeness of reports, and availability of research data. Data analysis was performed using IBM SPSS Statistics version 26 through descriptive statistics, classical assumption testing, multiple linear regression, and partial and simultaneous tests. The results show that Good Corporate Governance has a negative effect on Firm Value , while firm size , liquidity , and dividend payout ratio have no effect on Firm Value . Simultaneously, all independent variables have an effect on Firm Value . These findings indicate that the effectiveness of corporate governance is more decisive for investor assessment than the proportion of independent commissioners, while company size, liquidity, and dividend policy have not been the main factors in the formation of company value in IDX80 companies.